PENGARUH ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA) DAN OPERATING LEVERAGE TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2015-2017) - Erindia Cember; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACKThe objectives of this study are: 1). To find out the Economic Value Added effect on company stock returns (EVA), 2). To find out the Market Value Added (MVA) to the stock returns of mining companies, 3) to find out operating leverage against stock returns of mining companies. The population on this study were all industrial sectors of mining companies listed on the IDX for the period 2015-2017. The method used in this stud is the classic assumption test and multiple linear regression. With t test and f test as hypothesis testers. The result of this study Economic Value Added (EVA) has a positive and not significant effect, Market Value Added (MVA) has a positive and not significant effect, operating leverage has a positive and not significant effect. Keywords: stock prices, stock returns, economic value added, market value added, operating leverage.